Models of polycystic kidney disease in the rat - Gretz, Norbert; Haisch, S.; Baur, S.; Bauss, F.; Bachmann, Sebastian; Waldherr, Rüdiger; Strauch, Manfred (Experimental and genetic rat models of chronic renal failure, 1993)
04042015© Copyright 1993 by S. Karger AG1993Copyright / Drug Dosage / DisclaimerCopyright: All rights reserved. No part of this publication may be translated in